BEHAVIOR COUNSELING APPLICATION DESIGN USING DISC METHOD (DOMINANT, INFLUENCE, STEADY, COMPLIANCE) WEB-BASED IN BANDUNG'S HOLISTIC DEVELOPMENT COMMUNITY - Hidayat, Ramdhani; Tanzikisma, Nandi (RISTEC : Research in Information Systems and Technology, 2022)
Behavior counseling system using DISC method in the holistic development bandung community that is running in implementing a counseling counselor must come to the counseling place and must make an appointment to the counselor in terms of the time of counseling in technical implementation of counseling put together in one room there is no comfort in filling it because it is made in the same time then in terms of privacy it is not maintained so that the filling is less focused because in terms of charging it is not right wrong in filling in this problem is a picture of yourself then in filling must focus on knowing the results too long can take several hours or even one day, it is necessary to have a support application to speed up counseling services. The aim of the research is to facilitate the community and counselee in terms of counseling without having to come directly to the counseling place and is not limited by space and time and can speed up counseling services that have been consuming quite a long time. In this study using the Action Research and data collection techniquesused observation, interviews and literature studies while the design model used is the waterfall programming language PHP. The results of the research that were delivered include designing a website for counselees and admin design for counselees in the service of making it easy for the counselee to go to the web then log in for data security and fill in personal data if you don't have an account then you can see the company profile so that the counselee believesthat his personal data is guaranteed after the counselee is ready conduct counseling enter the counseling form and fil in a number of statements and the results can immediately be seen and can print out independently, the design for the admin is to be able to see counselees who do counseling on the website can be seen from the date the counselee wants to do counseling. The conclusions produced include a behavior counseling system that has used a more effective and efficient servant website and is beneficial to society at large.